The Function Of Imagery In The Qur'an: Surah Al-Kahf As A Model - Noor Kaled Muhyaldeen (Dzil Majaz: Journal of Arabic Literature, 2026)
This study aims to analyze the role of sound imagery in Surah Al-Kahf and its contribution to the aesthetic and rhetorical miracle of the Holy Qur’an. Surah Al-Kahf is considered one of the Qur’anic chapters rich in artistic, rhetorical, and acoustic expressions that create profound emotional and spiritual effects on readers and listeners. This research employs a descriptive analytical method by examining the phonetic and rhetorical aspects of selected verses in Surah Al-Kahf, including rhythm, repetition, Qur’anic pauses (fawasil), alliteration, and tonal harmony. The findings reveal that sound imagery in Surah Al-Kahf plays a significant role in strengthening meaning, enhancing emotional influence, and creating artistic harmony between sound and semantic context. The study also demonstrates that the Qur’anic sound system contributes to portraying scenes, emotions, and narrative movements in a vivid and impactful manner. Furthermore, the integration between phonetic patterns and rhetorical structures reflects the uniqueness and miraculous nature of Qur’anic discourse. Therefore, sound imagery in Surah Al-Kahf represents an important artistic element that highlights the beauty, eloquence, and spiritual influence of the Holy Qur’an